2007
DOI: 10.1002/chin.200710049
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Ruthenium‐Catalyzed Transfer Hydrogenation/Hydrogenation of 1,3‐Cycloalkanediones to 1,3‐Cycloalkanediols Using Microwave Heating.

Abstract: Hydrogenation O 0220 Efficient Ruthenium-Catalyzed Transfer Hydrogenation/Hydrogenation of 1,3-Cycloalkanediones to 1,3-Cycloalkanediols Using Microwave Heating. -(LEIJONDAHL, K.; FRANSSON, A.-B. L.; BAECKVALL*, J.-E.; J. Org. Chem. 71 (2006) 22, 8622-8625; Dep. Org. Chem., Arrhenius Lab., Univ. Stockholm, S-106 91 Stockholm, Swed.; Eng.) -Jannicke 10-049

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The well-established family of robust Noyori catalysts is very effective in terms of activity and stereoselectivity for ATH using either 2-PrOH or formic acid typically as the hydrogen source and for AH . This robustness of the Noyori catalysts promotes numerous applications in total synthesis and synthetic methodology as well as the development of many structural variations of these catalysts such as the introduction of the N - R -sulfonyl fragment, the sulfonamide moiety, the η 6 -arene ligand, or the diamine unit. , For example, in 1999 Ikariya’s group reported that a Noyori catalyst efficiently promoted the asymmetric reduction of 1,2-diphenylethane-1,2-dione (benzyl) with a substrate/catalyst molar ratio of 1000–2000 in mixed solvents consisting of formic acid and triethylamine, giving a series of ( R , R )-hydrobenzoin 18 quantitatively with high diastereomeric (97% de) and enantiomeric purities (>99% ee) (Scheme ). As chiral 1,2-diols, the ( R , R )-hydrobenzoins 18 are important building blocks in stereoselective organic syntheses as well as chiral ligands.…”
Section: Introductionmentioning
confidence: 99%
“…The well-established family of robust Noyori catalysts is very effective in terms of activity and stereoselectivity for ATH using either 2-PrOH or formic acid typically as the hydrogen source and for AH . This robustness of the Noyori catalysts promotes numerous applications in total synthesis and synthetic methodology as well as the development of many structural variations of these catalysts such as the introduction of the N - R -sulfonyl fragment, the sulfonamide moiety, the η 6 -arene ligand, or the diamine unit. , For example, in 1999 Ikariya’s group reported that a Noyori catalyst efficiently promoted the asymmetric reduction of 1,2-diphenylethane-1,2-dione (benzyl) with a substrate/catalyst molar ratio of 1000–2000 in mixed solvents consisting of formic acid and triethylamine, giving a series of ( R , R )-hydrobenzoin 18 quantitatively with high diastereomeric (97% de) and enantiomeric purities (>99% ee) (Scheme ). As chiral 1,2-diols, the ( R , R )-hydrobenzoins 18 are important building blocks in stereoselective organic syntheses as well as chiral ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the Ru(II) complexes bearing planar tridentate N 3 ligands and unsymmetrical planar tridentate ligands have been successfully developed and explored to construct the effective catalyst systems for the transfer hydrogenation of ketones [5][6][7][8][9][10]. In the study of the transfer hydrogenation mechanism, several ruthenium hydride complexes are considered as active species [11][12][13][14][15][16][17][18], but some ruthenium hydride complexes, such as RuHCl(PPh 3 ) 3 [11], are not the really active species. For the Ru(II) complexes bearing planar tridentate N 3 ligands, although some researchers regard the ruthenium hydride complexes as the real active species in the transfer hydrogenation of ketones [5][6][7][8][9][10], no ruthenium hydride complex has been isolated.…”
mentioning
confidence: 99%
“…Both showed low activities. Complex 2 exhibited a high transfer hydrogenation activity for pyridyl ketones (entries [15][16][17].…”
mentioning
confidence: 99%